Antifungal activity of Mongolian medicinal plant extracts. Issue 4 (16th February 2020) - Giordani, Cristiano; Simonetti, Giovanna; Natsagdorj, Damdinsuren; Choijamts, Gotov; Ghirga, Francesca; Calcaterra, Andrea; Quaglio, Deborah; De Angelis, Giulia; Toniolo, Chiara; Pasqua, Gabriella
Abstract: The in vitro antifungal activity of extracts obtained from 14 medicinal plants of the mongolian flora were investigated by measuring their minimal inhibitory concentration (MIC) against fungi cause of cutaneous diseases such as Candida species, dermatophytes and Malassezia furfur . Among the species examined, Stellaria dichotoma L., Scutellaria scordifolia L. Aquilegia sibirica Fisch. Et Schrenk. and Hyoscyamus niger L. extracts demonstrated antifungal activity against all studied fungi. In particular, S. scordifolia L. methanol extract, obtained at room temperature, showed the best activity against Candida spp., Malassezia furfur and dermatophytes with GMMIC50 values of 22 µg/mL, 64 µg/mL and 32 µg/mL, respectively. The flavones, luteolin and apigenin, identified in S. scordifolia extracts, and rutin identified in S. dichotoma and Hyoscyamus niger L. extracts, could be responsible of the observed antifungal activity. Graphical Abstract: